Structural equation model evaluating the impact of isolation and workfamily conflict on burnout among teleworking professionals - Maneechaeye, Pattarachat (Kasetsart Journal of Social Sciences, 2021)
The study of structural equation model evaluating the impact of isolation and work-family conflict on burnout among teleworking professionals aimed to scrutinize and investigate the casual relationship among isolation, work-family conflict and burnout. The research utilized a 2-step structural equation modelling technique based on review of related literature. The population and samples were selected from teleworking professionals in Thailand. Research tools were questionnaire with rating scales and a convenience sampling method was applied. The model fit, reliability and validity were analysed by using a confirmatory factor analysis. A causal relationship was analysed by structural model and path analysis. The results showed that the model was moderately fitted with empirical data and had an acceptable reliability and validity. The results yielded a positive direct effect of isolation on burnout. Moreover, work-family conflict acted as a partial mediator or indirect effect on the relationship between isolation and burnout. Based on these results, the organization should emphasize on employee work-life balance aspect even in a teleworking environment to mitigate work-family conflict risk. Furthermore, supervisors or managerial level employees should focus on communication among their subordinates even if they are working out of the office to mitigate isolation risk. Future research should be qualitative or mixed method to delve deep down for a richer qualitative interpretation and cohort or longitudinal research should be done in order to study these effects in the long run.